TREM2 suppresses the proinflammatory response to facilitate PRRSV infection via PI3K/NF-κB signaling - Zhu, Zhenbang (PLoS Pathog, 2020)
Triggering receptor expressed on myeloid cells 2 (TREM2) serves as an anti-inflammatory receptor, negatively regulating the innate immune response. TREM2 is mainly expressed on dendritic cells and macrophages, the target cells of porcine reproductive and respiratory syndrome virus (PRRSV). Thus, we investigated the potential role of TREM2 in PRRSV infection in porcine alveolar macrophages (PAMs). We found that there was an increased expression of TREM2 upon PRRSV infection in vitro. TREM2 silencing restrained the replication of PRRSV, whereas TREM2 overexpression facilitated viral replication. The cytoplasmic tail domain of TREM2 interacted with PRRSV Nsp2 to promote infection. TREM2 downregulation led to early activation of PI3K/NF-κB signaling, thus reinforcing the expression of proinflammatory cytokines and type I interferons. Due to the enhanced cytokine expression, a disintegrin and metalloproteinase 17 was activated to promote the cleavage of membrane CD163, which resulted in suppression of infection. Furthermore, exogenous soluble TREM2 (sTREM2)-mediated inhibition of PRRSV attachment might be attributed to its competitive binding to viral envelope proteins. In pigs, following PRRSV challenge in vivo, the expression of TREM2 in lungs and lymph nodes as well as the production of sTREM2 were significantly increased. These novel findings indicate that TREM2 plays a role in regulating PRRSV replication via the inflammatory response. Therefore, our work describes a novel antiviral mechanism against PRRSV infection and suggests that targeting TREM2 could be a new approach in the control of the PRRSV infection.